Data center storage cost-effective strategies, implementation, and management - Smith, Hubbert (Boca Raton, Fla. : Auerbach Publications, 2011)
"This work provides a storage industry insiders insight on how to properly scope, plan, evaluate, and implement storage technologies to maximize performance, capacity, reliability, and power savings. It covers all types of storage technology, including SAN, capacity-optimized drives, and solid-state drives. Written for IT managers, data center managers, and CIOs, the book offers strategies for minimizing risk and cost when implementing storage technology, including how to reduce air conditioning costs and overall power consumption. It also analyzes cloud technology and its effects on an organizations storage strategies"--
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Computer storage devices; Electronic data processing departments -- Management; Electronic books